Phase Line Attila : The Amphibious Campaign for Cyprus - Erickson, Edward J., 1950-; Uyar, Mesut (Book collections on Project MUSE., 2020)
"This monograph will prove to be one of the more valuable works ever written on the efficacy of modern era amphibious warfare. While many students of military affairs have assumed that large-scale forcible entry amphibious operations are a thing of the past, the authors have done an outstanding job, in just eight concise and well-written chapters, to demonstrate how amphibious warfare, in combination with other joint operations, can prove decisive on modern-day battlefields. Covering a little-known combat operation that incredibly involved two neighboring North Atlantic Treaty Organization (NATO) allies--Greece and Turkey--the 1974 battle known in Turkey as Operation Star Drop-4 and erroneously in the West as Operation Attila, took place on the perpetually restive island nation of Cyprus. Moreover, the authors have finally brought to light what is "arguably only one of two such [amphibious] operations" fought since 1945 that involved a substantially opposed landing. The operation also included the heavy use of airborne, airmobile, naval surface, and other follow-on armored forces that proved decisive toward relative Turkish success on Cyprus in 1974"--